Protective effects of ranolazine and propranolol, alone or combined, on the structural and functional alterations of cardiomyocyte mitochondria in a pig model of ischemia/reperfusion. (22nd April 2013) - Dehina, Leila; Descotes, Jacques; Chevalier, Philippe; Bui‐Xuan, Bernard; Romestaing, Caroline; Dizerens, Nicole; Mamou, Zahida; Timour, Quadiri
Abstract Preventing the consequences of ischemia/reperfusion (I/R)‐induced lesions in the clinic requires the administration of pharmacological agents prior to restoring coronary vascularization. The aim of this study was to evaluate the effects of ranolazine and propranolol when administered either alone or combined prior to I/R induction in a pig model. Thirty domestic pigs were randomly assigned to five groups of six animals including (i) sham animals; (ii) untreated animals with 45‐min ischemia and 1‐min reperfusion; animals administered intravenously with (iii) ranolazine, or (iv) propranolol, or (v) both combined, prior to 45‐min ischemia and 1‐min reperfusion. The heart rate (HR), duration of monophasic action potentials (dMAP), and peak of the time derivative of left ventricular pressure (LV dP/dt max) were measured during ischemia and after 1 min of reperfusion. Structural and functional parameters of mitochondria were analyzed in tissue samples taken from the left ventricle ischemic area at the end of the experiment. I/R induced expected effects, namely accelerated HR, decreased dMAP and LV dP/dt max, and altered mitochondrial structural and functional parameters including decreased oxygen consumption, increased reactive oxygen species (ROS) production, and reduced calcium retention capacity resulting in the opening of mitochondrial permeability transition pores (mPTP). Ranolazine and propranolol administered either alone or combined prior to I/R significantly decreased all of these deleterious consequences. The protective effects of ranolazine and propranolol are seemingly due to the prevention of calcium overload and resulting lesions in mitochondria.